2021
DOI: 10.1002/cpp.2633
|View full text |Cite
|
Sign up to set email alerts
|

The metacognitive model of post‐traumatic stress disorder and metacognitive therapy for post‐traumatic stress disorder: A systematic review

Abstract: The metacognitive model of post-traumatic stress disorder (PTSD) implicates metacognitive beliefs, meta-memory beliefs and metacognitive control strategies in perpetuating and maintaining symptoms of PTSD. Despite this expanding area of research, the evidence for the metacognitive model of PTSD has not been reviewed.A systematic review according to the PRISMA statement was conducted. Searches across MEDLINE, PubMed and PsycNET, as well as reference lists of the included studies (2004 to March 2020), yielded 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 52 publications
(246 reference statements)
0
18
0
Order By: Relevance
“…Furthermore, perceived stress was related to increased levels of anxiety, fear, and worry (Dymecka et al, 2021; Macatee et al, 2015; Masjoudi et al, 2022; Zajac et al, 2006). Worry, in turn, increase attention to the perceived threat and reduce the cognitive resources functional for effective emotional processing of a traumatic experience (Bardeen et al, 2013), becoming an important predictor of PTSD onset (Brown et al, 2022; Freeman et al, 2013). Following this perspective, PTSD can be read as an expression of difficulty in regulating and managing a state of distress due to one or more traumatic events, which results in both a biophysical and psychological alteration (Akiki et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, perceived stress was related to increased levels of anxiety, fear, and worry (Dymecka et al, 2021; Macatee et al, 2015; Masjoudi et al, 2022; Zajac et al, 2006). Worry, in turn, increase attention to the perceived threat and reduce the cognitive resources functional for effective emotional processing of a traumatic experience (Bardeen et al, 2013), becoming an important predictor of PTSD onset (Brown et al, 2022; Freeman et al, 2013). Following this perspective, PTSD can be read as an expression of difficulty in regulating and managing a state of distress due to one or more traumatic events, which results in both a biophysical and psychological alteration (Akiki et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis found that metacognitive therapy has been a promising avenue for treatment in depression and PTSD (Normann and Morina, 2018; see also Brown et al, 2022), though these therapies focus on regulating intrusive thoughts or metacognitive beliefs as measured in the MCQ (Wells 2008). Relevantly, positive beliefs around rumination (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Metacognitive Therapy (MCT), as developed by Wells and Sembi (2004), offers an alternative to direct trauma confrontations in prolonged exposure therapy or cognitive behavior therapy, and recent results are promising in comparison to prolonged exposure therapy (Wells and Colbear, 2012; see also Brown et al, 2022). However, studies involving MCT have not measured metacognitive bias or sensitivity, instead relying on the MCQ.…”
Section: Metacognition In Ptsdmentioning
confidence: 99%
“…In the past few years, many so‐called “Metacognitive Therapies” have been created to treat a vast range of psychiatric disorders, from schizophrenia to depression and anxiety disorders (Lysaker et al., 2020a ; Hoffart et al., 2018 ; Moritz et al., 2019 ; Brown et al., 2021 ). Further research needs to assess its potential impact on preventive measures regarding nonclinical samples.…”
Section: Discussionmentioning
confidence: 99%